(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Triggered by the corporate goal to brew the world from barley to bar and identified the input of human resource at it. The study looked at how human resource accounting affected the profitability of businesses with emphasis on Nigerian Breweries Plc. Disclosure of employee training cost, employee healthcare and employee welfare was used to measure human resource accounting, while profit after tax was employed to measure firm profitability. Ex post facto design was adopted to collect historic economic events of the firm for behavioural analysis. Data were obtained from annual reports from 2015 to 2024 by content analysis. Econometric models and residual estimation procedures were employed with the aid of e-views software. The analytical procedures involved descriptive statistics with Jacque-Bera test of data series, stationarity test to ascertain normality with Augmented Dickey fuller and Phillips-Perron, heteroskedasticity test with Breusch-Paga-Gregory model, multiple regression and hypothetical test. The results indicate the Log of employee training cost impacts significantly on Log of profit after tax. Similarly, Log of employee healthcare cost impacts significantly on the Log of profit after tax. However, the Log of employee welfare cost impacts insignificantly on the Log of profit after tax. The study concludes that investment in accounting for human resources significantly affects profitability, although the dimension of employee welfare was insignificant. It was therefore recommended that despite setbacks in measurement, human resource accounting practices should be integrated in the business model and financial reporting model of Nigerian Breweries Plc as it impact positively on the firm profitability.